2022
DOI: 10.1021/acscatal.2c00522
|View full text |Cite
|
Sign up to set email alerts
|

Rational Design of a De Novo Enzyme Cascade for Scalable Continuous Production of Antidepressant Prodrugs

Abstract: Natural products and their derivatives provide a promising source for drug discoveries. However, several natural products and derivatives are still difficult to advance to in vivo drug testing due to the requirement of an ample supply of drug candidates. Herein, we describe an immobilized enzyme cascade for the scalable continuous production of neuropharmaceutical prodrugs, L-4-chlorokynurenine (L-4-Cl-Kyn) and its non-natural analogue L-4-Br-Kyn. This synthetic route features a highly efficient one-pot C–H ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2022
2022
2025
2025

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 46 publications
0
12
0
Order By: Relevance
“…Enzyme Repositioning for Maximum Unlocking of New Catalytic Potential of Wild-Type Tryptophan 2,3-Dioxygenase (WT TDO): Old Path, New Frontier. As stated earlier, despite having developed an efficient and economical way to synthesize L-halokynurenine, 22 many potentially useful products, including L-Kyn analogues substituted at 3-, 5-, and 6-positions, are still challenging to obtain [Figure 1C(3)]. The limited product diversity is mainly due to the high specificity of tryptophan 2,3-dioxygenase (Tar13) used in this protocol, although Tar13 is the only tryptophan 2,3-dioxygenase reported so far that shows selectivity for chlorinated substrates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Enzyme Repositioning for Maximum Unlocking of New Catalytic Potential of Wild-Type Tryptophan 2,3-Dioxygenase (WT TDO): Old Path, New Frontier. As stated earlier, despite having developed an efficient and economical way to synthesize L-halokynurenine, 22 many potentially useful products, including L-Kyn analogues substituted at 3-, 5-, and 6-positions, are still challenging to obtain [Figure 1C(3)]. The limited product diversity is mainly due to the high specificity of tryptophan 2,3-dioxygenase (Tar13) used in this protocol, although Tar13 is the only tryptophan 2,3-dioxygenase reported so far that shows selectivity for chlorinated substrates.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…l -Kyn derivatives are a family of nonproteinogenic amino acids that exhibit diverse therapeutic properties in neurological disorders (Figure A). In addition, its non-natural analogue l -4-Cl-Kyn was recently identified as an amino acid building block in the lipopeptide antibiotics taromycin A and B (Figure B). , Because of their intriguing biological activities, a myriad of strategies have been employed to synthesize this pharmaceutical family. Although synthetic chemists and biologists have made significant progress in this field, there are still no productive methods known for industrialization.…”
Section: Introductionmentioning
confidence: 99%
“…Serine‐isotopologs can also be accepted by Pf TrpB 2B9 , which can be conveniently produced from deuterated formaldehyde and/or 13 C‐labelled glycine by L‐threonine aldolase to give tryptophan isotopologs with up to 4 isotope substitutions, on an analytical scale, augmenting previously described methods [32] . Pf TrpB 0A9 was applied in a cascade together with a ring‐opening tryptophan 2,3‐dioxygenase, Tar13, to produce chlorokynurenine and bromokynurenine, the former molecule being a current antidepressant drug candidate [33] . Co‐immobilisation of these two enzymes gave a heterogeneous catalyst capable of producing hundreds of milligrams of the products, but activity was rapidly lost upon catalyst‐recycling.…”
Section: Tryptophan Synthase and Tyrosine Phenol Lyasementioning
confidence: 99%
“…[32] Pf TrpB 0A9 was applied in a cascade together with a ring‐opening tryptophan 2,3‐dioxygenase, Tar13, to produce chlorokynurenine and bromokynurenine, the former molecule being a current antidepressant drug candidate. [33] Co‐immobilisation of these two enzymes gave a heterogeneous catalyst capable of producing hundreds of milligrams of the products, but activity was rapidly lost upon catalyst‐recycling. The same study demonstrated the antidepressant properties of both chlorokynurenine and bromokynurenine in mice.…”
Section: Tryptophan Synthase and Tyrosine Phenol Lyasementioning
confidence: 99%
“…The use of enzymes as catalysts for biosynthesis of chemical compounds is popular in the manufacturing of pharmaceuticals and active pharmaceutical ingredients. Generally, biocatalysts are appealing for pharmaceutical manufacturing because their high enantio-, regio- and chemoselectivities reduce the generation of undesired side products. Furthermore, biocatalysts are usually used under mild and environmentally friendly conditions, which means that enzymatic biotransformations are more sustainable compared with conventional chemical syntheses. , Nevertheless, the application of enzymatic systems can be limited by low reaction efficiencies, enzyme instability, and tedious optimization and scale-up processes. , …”
Section: Introductionmentioning
confidence: 99%